اثر موقع لانستغرام في زيادة مبيعات اصحاب الحرف - عائشة بن عية; د/ حرزالله شوشة (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة: جاءت دراستنا بعنوان اثرموقعالاستغرامفيزيادةمبيعاتأصحابالحرف- دراسةميدانيةعلىمجموعةمنحرفيمدينةالاغواط- وانطلقت دراستنا من الإشكالية: هل يؤثر التسويق الالكتروني على أصحاب الحرف وزيادة مبيعاتهم؟ وتتفرع الإشكالية العامة للدراسة إلى مجموعة من التساؤلات الفرعية تتمثل في: 1. هل يوجد اهتمام بالخدمات التسويقية زيادة مبيعات أصحاب الحرف؟ 2. هل يقوم بتسويق ما يرغب فيه أصحاب الحرف؟ 3. هل يتفاعل أصحاب الحرف مع منشورات التسويق الالكتروني من خلال موقع الانستغرام؟ ومنه تم استنتاج الفرضيات التالية: 1. يوجد اهتمام بالخدمات التسويقية زيادة مبيعات أصحاب الحرف 2. يقوم بتسويق ما يرغب فيه أصحاب الحرف 3. يتفاعل أصحاب الحرف مع منشورات التسويق الالكتروني من خلال موقع الانستغرام نهدف من خلال دراستنا الى التعرف على أراءالمبحوثين اتجاه الدور الذي يلعبه الانستغرام في الخدمات التسويقية والتأكيد على الأهمية الكبرى التي يلعبها الانستغرام وتسويق مبيعات أصحاب الحرف. وفي دراستنا اعتمدنا على المنهج الوصفي وأداة جمع البيانات تمثلت في الاستبيان لدراسة مجتمع الدراسة المتكون من 20 حرفي من حرفي مدينة الأغواط حيث توصلنا الى النتائج التالية: 1. استخدام الحرفيين لموقع Instagram زاد من مبيعاتهم لمنتوجاتهم الحرفية من خلال تسويقها الكترونيا واظهارها بصور والفيديوهات ومراحل الصنع للزبائن من اجل استقطابهم. 2. موقع Instagram تأثير إيجابي على نشاط الحرفي كونه وسيلة ترويج الكترونية مجانية تضمن للحرفي ترويج وتسويق منتوجاته الحرفية واظهارها لعدد كبير من الزبائن نظرا للاستخدام الواسع للموقع في المجتمع. 3. أكثر حرفيي مدينة الاغواط دائما ما يستخدمون موقع Instagram في تسويق منتجات الحرفين وعرضها بغرض ايصالها لاكبر عدد ممكن من الزبائن لزيادة المبيعات. 4. هناك العديد من الدوافع لاستخدام موقع التواصل الاجتماعي Instagram وأكثرها التسويقية والإخبارية والاجتماعية وبدرجة اقل دوافع التعليمية والترفيهية والتثقيفية كما ان الوسيلة المفضل لتصفح موقع التواصل الاجتماعي Instagram هو الهاتف الذكي. Study summary Our study was entitled The Impact of Instagram on Increasing the Sales of Craftsmen - A Field Study on a Group of Craftsmen in the City of Laghouat - and our study started from the problem: Does electronic marketing affect craftspeople and increase their sales? The general problem of the study is divided into a set of sub-questions: 1. Is there interest in marketing services to increase sales of craft owners? 2. Does it market what craftsmen desire? 3. Do craftspeople interact with electronic marketing posts through Instagram? From this, the following hypotheses were concluded: 1. There is interest in marketing services to increase sales of craftsmen 2. It markets what craftsmen desire 3. Craftsmen interact with electronic marketing posts through Instagram Through our study, we aim to identify the opinions of the respondents regarding the role that Instagram plays in marketing services and to emphasize the great importance that Instagram plays and marketing the sales of craftsmen. In our study, we relied on the descriptive approach and the data collection tool, which was the questionnaire, to study the study population consisting of 20 craftsmen from the city of Laghouat, where we reached the following results: 1. Craftsmen’s use of Instagram increased their sales of their craft products by marketing them electronically and showing them with pictures, videos, and manufacturing stages to customers in order to attract them. 2. Instagram has a positive impact on the craftsman’s activity, as it is a free electronic promotional means that ensures the craftsman can promote and market his craft products and display them to a large number of customers due to the widespread use of the site in society. 3. Most of the craftsmen in the city of Laghouat always use Instagram to market and display the craftsmen’s products with the aim of delivering them to the largest possible number of customers to increase sales. 4. There are many reasons for using the social networking site Instagram, most of which are marketing, news, and social, and to a lesser extent educational, entertainment, and cultural motives. The preferred means of browsing the social networking site Instagram is the smartphone.
دراسة ميدانية على مجموعة من حرفي مدينة الاغواط